Exploring how rubric training influences students' assessment and awareness of interpreting. Issue 2 (2nd April 2020) - Su, Wei
Abstract: Previous studies explored how rubrics of writing and speaking could change students' self assessment and awareness of language skills, yet few disclosed the benefits of rubrics of interpreting. To close the gap, the present paper tapped the effects of rubric training in students' self assessment and awareness of interpreting. After giving a three-week rubric training on Chinese-English interpreting to 32 Chinese undergraduates, it was found that students were able to simultaneously attend to multiple criteria, as they circled more descriptor words from the rubric and generated more numerous and elaborate comments. In addition, their assessments were extended from local, negative comments to global, positive ones, indicating their balanced and hierarchical thinking of interpreting skills. Post-training self reports revealed that rubric training improved their understanding and learning of interpreting skills, forming a favourable cycle of assessment-awareness-acquisition. Future pedagogical suggestions were proposed accordingly.